The Study of Temperature Effects On Activated Sludge Stability and it’s Dewaterability by using bioelectricity cell as a treatment unit. - Jasim Mohamed, Samaher (Anbar Journal of Engineering Sciences, 2012)
%95.21 in (25 c°, 35 c°, 45 c°). In the anaerobic treatment SRF is reduction by percent %91.65, %97.25, %92.7 in (25 c°, 35 c°, 45 c°). Percent reduction of dry solid (DS) concentration in the aerobic treatment is %7.61, %9.3 in (25c°, 35c°, 45c°) respectively. While in the aerobic treatment the percent reduced of DS was %75, %51, %16 respectively with (25c°, 35c°, 45c°). The results showed the effect of aerobic and anaerobic treatments of activated sludge with three different temperatures (25c°, 35c°, 45c°), on the dewatering of sludge and its stability and the hydraulic detention time with using bioelectricity cell. The study outcomes revealed that the biological treatment is enhanced dewaterability of the activated sludge for aerobic and anaerobic treatment, in the aerobic treatment the specific resistance to filtration (SRF) is reduction by percent%95.7.